2019
DOI: 10.1371/journal.pmed.1002724
|View full text |Cite
|
Sign up to set email alerts
|

The influence of obesity-related factors in the etiology of renal cell carcinoma—A mendelian randomization study

Abstract: BackgroundSeveral obesity-related factors have been associated with renal cell carcinoma (RCC), but it is unclear which individual factors directly influence risk. We addressed this question using genetic markers as proxies for putative risk factors and evaluated their relation to RCC risk in a mendelian randomization (MR) framework. This methodology limits bias due to confounding and is not affected by reverse causation.Methods and findingsGenetic markers associated with obesity measures, blood pressure, lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 37 publications
3
63
0
1
Order By: Relevance
“…For breast, prostate, renal, and thyroid cancers, we estimated the expected impact of obesity by including estimates of changes in relative risk with increasing body mass index (BMI), based on Australian mean BMI data …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For breast, prostate, renal, and thyroid cancers, we estimated the expected impact of obesity by including estimates of changes in relative risk with increasing body mass index (BMI), based on Australian mean BMI data …”
Section: Methodsmentioning
confidence: 99%
“…For renal cancer, the relative risk has been reported to increase by 56% per standard deviation rise in BMI, but this finding may have been influenced by investigation rates. 25 Based on changes in mean BMI in Australia from 1989 to 2012, 27 this yields relative risks of 1.56 × 1.8/7.5 or 1.13 for women and 1.56 × 1.8/5.2 or 1.19 for men. Were these estimates used for the expected increase in lifetime probability, overdiagnosis rates would be modestly smaller than the 58% (women) and 42% (men) we report.…”
Section: Potential Effects Of Changes In Body-mass Indexmentioning
confidence: 99%
“…However, in their study, high serum IGF-1 levels at the time of diagnosis correlated with favourable prognosis; therefore, it seems that serum IGF-1 level may be an independent prognostic factor of renal cell carcinoma. In contrast, Johansson et al [ 61 ] demonstrated significant association between the variables related to fasting insulin and RCC risk. In their Mendelian randomization study, one standard deviation (SD) increment in fasting insulin increased the risk of RCC by 82%.…”
Section: Insulin Resistancementioning
confidence: 91%
“…Zhang et al [ 60 ] suggested that the stabilization of hypoxia-inducible factors and inhibition of insulin-like growth factor receptor 1 signalling resulting from von Hippel-Lindau syndrome is the essential mechanism in RCC biology. According to Johansson et al [ 61 ], insulin resistance may lead to compensatory hyperinsulinemia resulting from enhanced insulin secretion by pancreatic β-cells to maintain normal blood glucose. It has been hypothesized that hyperinsulinemia may augment cancer cell growth and proliferation through insulin action via its receptor and the activation of IGF pathway [ 62 ].…”
Section: Insulin Resistancementioning
confidence: 99%
“…For breast, 23 prostate, 24 renal, 25 and thyroid cancers, 26 we estimated the expected impact of obesity by including estimates of changes in relative risk with increasing body mass index (BMI), based on Australian mean BMI data. 27…”
Section: Potential Effects Of Changes In Body Mass Indexmentioning
confidence: 99%